Teachers’ beliefs related to language choice in immigrant students’ homes - Alisaari Jenni; Sissonen Salla; Heikkola Leena Maria (Elsevier, 2025)
This study investigates how Finnish teachers regard immigrant families’ home language policies. Of the teachers who responded, 53.3% believed it best for parents to speak their first languages at home, and 31.7% believed that both first language and language of instruction should be used at home. A minority of the teachers believed that only Finnish should be spoken at home. The teachers’ justifications for their beliefs reflected Ruiz’s (1984) orientations in language planning: language-as-right, language-as-resource, and language-as-problem, with most teachers oriented toward language-as-resource. Thus, many teachers’ beliefs align with the current educational stance of supporting multilingualism.